Aluminium detoxification in facultative (Passovia ovata (Pohl ex DC.) Kuijt and Struthanthus polyanthus Mart. - Loranthaceae) and dependent (Psittacanthus robustus (Mart.) Marloth - Loranthaceae) Al-accumulating mistletoe species from the Brazilian savanna. (September 2018) - de Souza, Marcelo Claro; Scalon, Marina Corrêa; Poschenrieder, Charlotte; Tolrà, Roser; Venâncio, Tiago; Teixeira, Simone Pádua; Da Costa, Fernando Batista
Abstract: Mechanisms to detoxify aluminium (Al) is a hot topic for cultivated plants. However, little information is known about the mechanisms used by native plants to deal with Al-toxicity. In Cerrado, some generalist mistletoe species, such as Passovia ovata (Pohl ex DC.) Kuijt and Struthanthus polyanthus Mart. can parasitize Al-accumulating and Al-excluding plant species without any clear symptoms of toxicity and mineral deficiency, while Psittacanthus robustus (Mart.) Marloth, a more specialist mistletoe, seems to be an Al-dependent species, parasitizing only Al-accumulating hosts. Here we (i) characterized the forms and compartmentalization of Al in leaves of P. robustus ; (ii) compared Ca and Al leaf concentration, and leaf concentration of organic acids and polyphenols between facultative Al-accumulating ( P. ovata and S. polyanthus ) and Al-dependent ( P. robustus ) mistletoe species infecting Miconia albicans (Sw.) Steud. (Al-accumulating species). P. robustus chelated Al 3+ with oxalate and stored it in the phloematic and epidermic leaf tissues. Leaf Ca and Al concentration did not differ among species. Leaf oxalate concentration was higher in the Al-dependent species. Concentrations of citrate and phenolic compounds were higher in the leaves of the facultative Al-accumulating species. These results show that facultative Al-accumulating and Al-dependent species use different mechanisms to detoxify Al. Moreover, this is the first report on a mistletoes species ( P. robustus ) with a potential calcifuge behaviour in Cerrado. Graphical abstract: Highlights: Facultative Al-accumulating mistletoe species detoxify Al with citrate. Al-dependent mistletoe species detoxify Al with oxalate. Psittacanthus robustus store Al in the phloematic and epidermic leaf tissues. Psittacanthus robustus is a mistletoe species with a calcifuge behaviour.